Germanium-based negative electrode material and preparation method and application thereof

By depositing germanium-based composite particles on the porous polyaniline template and forming a carbon cladding layer, the deformation and damage of electrode materials caused by volume changes during charging and discharging of germanium-based negative electrode materials is solved, and high energy density and long cycle life are achieved and stable germanium-based anode material.

CN119495721APending Publication Date: 2025-02-21LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311060941.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Volume expansion and contraction of germanium-based negative electrode materials during charging and discharging leads to deformation and damage of the electrode materials, affecting battery life and stability, and the conductivity and cyclic stability need to be optimized.

Method used

Porous polyaniline is used as a template to deposit germanium-based composite particles by vapor deposition method, and a carbon cladding layer is formed on their surface to form a germanium-based negative electrode material. This material optimizes the formation of germanium-based composite particles through the pore structure of porous polyaniline, improves electrochemical activity, and improves the stability of the material through a carbon cladding layer.

Benefits of technology

It improves the energy density and energy storage performance of germanium-based anode material, extends the cycle life of the battery, enhances the structural stability of the material, and optimizes the conductivity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495721A_ABST
    Figure CN119495721A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a germanium-based negative electrode material as well as a preparation method and application thereof. The germanium-based negative electrode material comprises germanium-based composite particles and a carbon coating layer coating the outer surfaces of the germanium-based composite particles, pores of the porous polyaniline form continuous channels and spaces in the porous polyaniline, so that germanium-containing sediments are deposited in the pores of the porous polyaniline to form germanium-based composite particles; the mass percent of the porous polyaniline in the germanium-based composite particles is 15%-95%; the germanium-containing sediment at least comprises elemental germanium, and also comprises or does not comprise silicon-germanium alloy and / or tin-germanium alloy; in the germanium-based negative electrode material, the germanium-based composite particles account for 85%-99% by mass; the germanium elementary substance accounts for 0.1-80% of the germanium-based negative electrode material in percentage by mass; the silicon-germanium alloy or the tin-germanium alloy accounts for 0-15% of the germanium-based negative electrode material in percentage by mass; polar groups-NH <-> and = N <-> of porous polyaniline are used for promoting adsorption and intercalation of lithium ions or sodium ions, active sites of the negative electrode material are increased in the charging and discharging process of the battery, and the electrochemical activity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary battery materials, and in particular to a germanium-based negative electrode material and a preparation method and application thereof. Background Art

[0002] With the continuous development of mobile electronic devices, electric vehicles and renewable energy, the demand for high-performance energy storage systems has gradually increased. Lithium-ion batteries and sodium-ion batteries have received extensive attention as two important energy storage technologies. As high energy density and environmentally friendly battery technologies, they have been widely used in mobile devices, electric vehicles and energy storage systems.

[0003] However, with the increasing demand for applications, traditional lithium / sodium-ion batteries face several challenges, such as limitations in energy density, charge and discharge rates, lifespan, and safety. In order to meet the growing energy demand, researchers are constantly seeking new electrode materials to improve battery performance and address these challenges.

[0004] In this context, germanium, as a material with high energy density and conductivity, has gradually attracted research attention. Germanium has a high theoretical capacity and can embed more lithium / sodium ions, thereby improving the energy storage capacity of the battery. In addition, the flexibility of germanium in chemical structure also provides opportunities for its application in battery materials. Through reasonable design and regulation, better electrochemical performance can be achieved.

[0005] However, germanium-based negative electrode materials still face some problems in practical applications. The volume expansion and contraction of germanium will cause deformation and damage of electrode materials during the charging and discharging process, thus affecting the life and stability of the battery. In addition, the conductivity and cycle stability of germanium-based materials also need to be further optimized.

[0006] Therefore, researchers are seeking innovative germanium-based anode materials to address these challenges and improve the performance of germanium-based anode materials in energy storage systems such as secondary ion batteries. Summary of the invention

[0007] The purpose of the present invention is to provide a germanium-based negative electrode material and a preparation method and application thereof, so as to improve the energy density and energy storage performance of germanium-based negative electrode material batteries and improve the stability and cycle life of electrode materials.

[0008] To this end, in a first aspect, an embodiment of the present invention provides a germanium-based negative electrode material, comprising: a germanium-based composite particle and a carbon coating layer coated on the outer surface of the germanium-based composite particle;

[0009] The pores of the porous polyaniline form continuous channels and spaces inside the porous polyaniline, so that the germanium-containing sediment is deposited in the pores of the porous polyaniline to form the germanium-based composite particles; in the germanium-based composite particles, the porous polyaniline accounts for 15%-95% by mass; the germanium-containing sediment includes at least a single substance of germanium, and may also include or exclude a silicon-germanium alloy and / or a tin-germanium alloy;

[0010] In the germanium-based negative electrode material, the mass percentage of the germanium-based composite particles is 85%-99%;

[0011] The mass percentage of the germanium single substance in the germanium-based negative electrode material is 0.1%-80%; the mass percentage of the silicon-germanium alloy in the germanium-based negative electrode material is 0-15%; the mass percentage of the tin-germanium alloy in the germanium-based negative electrode material is 0-15%;

[0012] The polar groups -NH- and =N- of the porous polyaniline are used to promote the adsorption and intercalation of lithium ions or sodium ions, thereby increasing the active sites of the negative electrode material and improving the electrochemical activity during the charge and discharge process of the battery.

[0013] Preferably, the particle size D of the porous polyaniline is 50 The diameter of the pores of the porous polyaniline is between 50nm and 50μm; the pore size of the pores of the porous polyaniline is between 1nm and 300nm; and the porosity of the porous polyaniline is between 20% and 90%.

[0014] Preferably, the mass of the germanium single substance accounts for 3%-30% of the total mass of the germanium-based negative electrode material;

[0015] The mass of the carbon coating layer accounts for 1%-15% of the total mass of the germanium-based negative electrode material;

[0016] The germanium-based composite material is obtained by decomposing a germanium source material by vapor deposition and depositing a germanium-containing precipitate in the pores of the porous polyaniline; the germanium source material at least includes germane and may include or exclude vaporized silicon germanium and / or vaporized tin germanium.

[0017] In a second aspect, an embodiment of the present invention provides a method for preparing the germanium-based negative electrode material according to the first aspect, the preparation method comprising:

[0018] The porous polyaniline is placed in a deposition chamber of a vapor deposition furnace and an inert environment is maintained;

[0019] A mixed gas of a germanium source material and an inert gas is introduced into a deposition chamber, and the germanium source material forms a germanium-containing precipitate which is deposited in the pores of the porous polyaniline to obtain germanium-based composite particles;

[0020] The germanium-based composite material particles are subjected to carbon coating treatment in a coating furnace to form a carbon coating layer, thereby obtaining a germanium-based negative electrode material.

[0021] Preferably, the germanium source material includes at least germane, and may include or exclude vaporized silicon germanium and / or vaporized tin germanium;

[0022] The inert gas includes nitrogen and / or argon; the time for introducing the mixed gas is 30 minutes to 12 hours;

[0023] The mass ratio of the germanium source material to the inert gas in the mixed gas is 1:1-1:10.

[0024] Preferably, when the germanium source material only includes germane, the germanium source material and an inert gas are introduced into the deposition chamber, and the germanium source material forms a germanium-containing precipitate which is deposited in the pores of the porous polyaniline to obtain the germanium-based composite particles. Specifically, the mixed gas of germane and an inert gas is introduced into the deposition chamber, and the temperature is kept at 350° C.-360° C. to decompose germane into a single germanium substance, and the single germanium substance is deposited in the pores of the porous polyaniline, and then calcined at 560° C. to obtain a germanium-based composite material.

[0025] When the germanium source material only includes germane and vaporized silicon germanium and / or vaporized tin germanium, a mixed gas of the germanium source material and an inert gas is introduced into a deposition chamber, and the germanium source material forms a germanium-containing sediment which is deposited in the pores of the porous polyaniline to obtain germanium-based composite particles. Specifically, the following steps are performed: a mixed gas of germane and vaporized silicon germanium and / or vaporized tin germanium and an inert gas is introduced into the deposition chamber, and the chamber is kept warm at 350°C-360°C to decompose germane into a single germanium substance, and the single germanium substance is deposited in the pores of the porous polyaniline together with the silicon germanium / tin germanium, and then calcined at 560°C to obtain a germanium-based composite material.

[0026] Preferably, the carbon coating treatment method includes: one of gas phase coating, liquid phase coating or solid phase coating;

[0027] The mass of the carbon coating layer accounts for 1%-15% of the total mass of the germanium-based negative electrode material;

[0028] The carbon material used for the liquid phase coating or solid phase coating includes one or more of glucose, sucrose, liquid asphalt, phenolic resin, polyvinylidene fluoride, citric acid, polyacrylonitrile, and polyvinyl alcohol;

[0029] The carbon material used for gas phase coating includes one or more of methane, ethylene, propylene, acetylene and natural gas.

[0030] In a third aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the germanium-based negative electrode material described in the first aspect.

[0031] In a fourth aspect, an embodiment of the present invention provides a secondary battery, comprising the negative electrode plate described in the third aspect.

[0032] Preferably, the secondary battery includes a lithium ion battery and a sodium ion battery.

[0033] The germanium-based negative electrode material provided by the embodiment of the present invention can bring significant innovation and improvement in the field of germanium-based negative electrode materials, mainly including:

[0034] 1. Provide high energy density and energy storage performance: By introducing the combination of germanium-based composite particles and porous polyaniline, the pore structure of porous polyaniline can be optimized for the formation of germanium-based composite particles. Such a combination can not only provide a larger surface area and increase the contact area between the electrode and the electrolyte, but also help to embed lithium ions or sodium ions, thereby improving the energy density and energy storage performance of the battery.

[0035] 2. Improve the stability and cycle life of electrode materials: The carbon coating layer as a protective layer on the outer surface can prevent the volume change of germanium-based composite particles and the destruction of the solid electrolyte interface during the charge and discharge process to a certain extent, which helps to slow down the attenuation rate of the electrode material and improve the cycle life of the battery.

[0036] 3. Integrate the advantages of multi-element alloy materials: By selecting a combination of germanium, silicon-germanium alloy and tin-germanium alloy, multiple advantages can be obtained in material performance. Different alloy components can provide different embedding and release capabilities during the battery charging and discharging process, thereby further optimizing battery performance.

[0037] 4. Improved electrochemical activity: The polar groups (-NH- and =N-) in porous polyaniline can promote the adsorption and intercalation of lithium or sodium ions, thereby increasing the active sites of the negative electrode material. This can significantly improve the energy density and electrochemical activity of the battery.

[0038] 5. Improve the structural stability of the material: Use the pores of porous polyaniline as a template to deposit germanium to obtain nano-sized germanium. The germanium particle size is small and the deformation is anisotropic when it expands, which can significantly reduce stress and strain and prevent structural damage.

[0039] 6. Material preparation and engineering feasibility: The material preparation method involved in the technical solution of the present invention is easy to implement and has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A schematic diagram of the structure of germanium-based composite particles in a germanium-based negative electrode material provided in an embodiment of the present invention;

[0041] Figure 2 Flow chart of the method for preparing germanium-based negative electrode material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0043] The embodiment of the present invention provides a germanium-based negative electrode, wherein the germanium-based negative electrode material comprises: germanium-based composite particles and a carbon coating layer coated on the outer surface of the germanium-based composite particles;

[0044] The schematic diagram of the structure of germanium-based composite particles is as follows Figure 1 As shown, the pores of the porous polyaniline form continuous channels and spaces inside the porous polyaniline, which are used for the germanium-containing sediment to be deposited in the pores of the porous polyaniline to form the germanium-based composite particles; in the germanium-based composite particles, the mass percentage of the porous polyaniline is 15%-95%; the germanium-containing sediment at least includes a single substance of germanium, and may also include or exclude a silicon-germanium alloy and / or a tin-germanium alloy; the germanium-based composite material is obtained by decomposing a germanium source material by a vapor deposition method and depositing the germanium-containing sediment in the pores of the porous polyaniline; the germanium source material at least includes germane, and may also include or exclude vaporized silicon-germanium and / or vaporized tin-germanium.

[0045] In the germanium-based negative electrode material, the mass percentage of germanium-based composite particles is 85%-99%;

[0046] The mass percentage of the germanium element in the germanium-based negative electrode material is 0.1%-80%, more preferably 3%-30%; the mass percentage of the silicon-germanium alloy in the germanium-based negative electrode material is 0-15%; the mass percentage of the tin-germanium alloy in the germanium-based negative electrode material is 0-15%;

[0047] The mass of the carbon coating layer accounts for 1%-15% of the total mass of the germanium-based negative electrode material;

[0048] The polar groups -NH- and =N- of porous polyaniline are used to promote the adsorption and intercalation of lithium ions or sodium ions, thereby increasing the active sites of the negative electrode material and improving the electrochemical activity during the charge and discharge process of the battery.

[0049] Furthermore, the particle size D of porous polyaniline 50 The diameter of the pores of the porous polyaniline is between 50nm and 50μm; the pore size of the porous polyaniline is between 1nm and 300nm; and the porosity of the porous polyaniline is between 20% and 90%.

[0050] The above materials can be prepared according to the following method, the main steps are as follows: Figure 2 As shown, including:

[0051] Step 110, placing porous polyaniline in a deposition chamber of a vapor deposition furnace and maintaining an inert environment;

[0052] The inert environment can be a nitrogen environment or an argon environment.

[0053] Step 120, introducing a mixed gas of a germanium source material and an inert gas into a deposition chamber, so that the germanium source material forms a germanium-containing precipitate which is deposited in the pores of the porous polyaniline to obtain germanium-based composite particles;

[0054] Wherein, the germanium source material includes at least germane, and may include or exclude vaporized silicon germanium and / or vaporized tin germanium;

[0055] The inert gas includes nitrogen and / or argon; the mass ratio of the germanium source material to the inert gas in the mixed gas is 1:1-1:10; and the time for introducing the mixed gas is 30 minutes-12 hours.

[0056] When the germanium source material only includes germane, a mixed gas of the germanium source material and an inert gas is introduced into the deposition chamber, and the germanium source material forms a germanium-containing sediment which is deposited in the pores of the porous polyaniline to obtain germanium-based composite particles. Specifically, the mixed gas of germane and the inert gas is introduced into the deposition chamber, and the temperature is kept at 350° C.-360° C. for 30 minutes-5 hours to decompose germane into a single germanium substance, and the single germanium substance is deposited in the pores of the porous polyaniline, and then calcined at 560° C. for 1-12 hours to obtain a germanium-based composite material;

[0057] When the germanium source material only includes germane and vaporized silicon germanium and / or vaporized tin germanium, a mixed gas of the germanium source material and an inert gas is introduced into a deposition chamber, and the germanium source material forms a germanium-containing sediment that is deposited in the pores of the porous polyaniline to obtain germanium-based composite particles. Specifically, the method comprises the following steps: introducing a mixed gas of germane and vaporized silicon germanium and / or vaporized tin germanium and an inert gas into the deposition chamber, and keeping the temperature at 350° C.-360° C. for 30 minutes-5 hours to decompose germane into a single germanium substance, and the single germanium substance is deposited in the pores of the porous polyaniline together with the silicon germanium / tin germanium, and then calcining the mixture at 560° C. for 1-12 hours to obtain a germanium-based composite material.

[0058] Of course, the calcination temperature can also be adjusted according to needs, which is a routine operation of those skilled in the art. The calcination at 560° C. proposed here is only an example of a specific implementation method and is not intended to limit the present invention to only being able to achieve calcination at this temperature.

[0059] Step 130 , subjecting the germanium-based composite material particles to carbon coating treatment in a coating furnace to form a carbon coating layer, thereby obtaining a germanium-based negative electrode material.

[0060] The carbon coating treatment method includes: one of gas phase coating, liquid phase coating or solid phase coating; the mass of the carbon coating layer accounts for 1%-15% of the total mass of the germanium-based negative electrode material.

[0061] Specifically, the carbon materials used for liquid phase coating or solid phase coating include: one or more of glucose, sucrose, liquid asphalt, phenolic resin, polyvinylidene fluoride, citric acid, polyacrylonitrile, and polyvinyl alcohol; the carbon materials used for gas phase coating include: one or more of methane, ethylene, propylene, acetylene, and natural gas.

[0062] The germanium-based negative electrode material prepared by the present invention can be used to prepare the negative electrode plate of a secondary battery, for example, as the negative electrode plate of a lithium ion battery or the negative electrode plate of a sodium ion battery.

[0063] The germanium-based negative electrode material provided by the embodiment of the present invention can bring significant innovation and improvement in the field of germanium-based negative electrode materials, mainly including:

[0064] 1. Provide high energy density and energy storage performance: By introducing the combination of germanium-based composite particles and porous polyaniline, the pore structure of porous polyaniline can be optimized for the formation of germanium-based composite particles. Such a combination can not only provide a larger surface area and increase the contact area between the electrode and the electrolyte, but also help to embed lithium ions or sodium ions, thereby improving the energy density and energy storage performance of the battery.

[0065] 2. Improve the stability and cycle life of electrode materials: The carbon coating layer as a protective layer on the outer surface can prevent the volume change of germanium-based composite particles and the destruction of the solid electrolyte interface during the charge and discharge process to a certain extent, which helps to slow down the attenuation rate of the electrode material and improve the cycle life of the battery.

[0066] 3. Integrate the advantages of multi-element alloy materials: By selecting a combination of germanium, silicon-germanium alloy and tin-germanium alloy, multiple advantages can be obtained in material performance. Different alloy components can provide different embedding and release capabilities during the battery charging and discharging process, thereby further optimizing battery performance.

[0067] 4. Improved electrochemical activity: The polar groups (-NH- and =N-) in porous polyaniline can promote the adsorption and intercalation of lithium or sodium ions, thereby increasing the active sites of the negative electrode material. This can significantly improve the energy density and electrochemical activity of the battery.

[0068] 5. Improve the structural stability of the material: Use the pores of porous polyaniline as a template to deposit germanium to obtain nano-sized germanium. The germanium particle size is small and the deformation is anisotropic when it expands, which can significantly reduce stress and strain and prevent structural damage.

[0069] 6. Material preparation and engineering feasibility: The material preparation method involved in the technical solution of the present invention is easy to implement and has good prospects for industrial application.

[0070] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the germanium-based negative electrode material of the present invention are respectively described below with multiple specific examples.

[0071] Example 1

[0072] This embodiment provides a preparation process and performance test of a germanium-based negative electrode material. The specific preparation process is as follows.

[0073] (1) At room temperature, 2.5 kg of porous polyaniline is placed in a deposition chamber of a vapor deposition furnace, and nitrogen is introduced into the vapor deposition furnace to exhaust air; wherein the porosity of the porous polyaniline is 30%, and the pore size of the porous polyaniline is in the range of 3 nm-10 nm.

[0074] (2) Turn off the nitrogen gas used for evacuation, raise the temperature to 360° C., and introduce a mixed gas of germane and nitrogen with a mass ratio of 1:1 into the deposition chamber for 1 hour. The germanium obtained by decomposing germane at 360° C. is deposited in the pores of the porous polyaniline, and then calcined at 560° C. for 2 hours to obtain a germanium-based composite material.

[0075] (3) The above germanium-based composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer on the surface of the germanium-based composite material. The specific method is as follows: 2.5 kg of the germanium-based composite material is placed in a rotary kiln, the temperature is raised to 360° C. under a nitrogen atmosphere, argon gas and acetylene gas are introduced at a volume ratio of 1:1.5 for gas phase coating, the organic gas source is turned off after keeping the temperature for 3 hours, the material is cooled to room temperature and then discharged and classified to obtain a germanium-based negative electrode material with a core-shell structure.

[0076] The mass of germanium accounts for 8% of the total mass of the germanium-based negative electrode material.

[0077] The germanium-based negative electrode material prepared in this embodiment was used to prepare a negative electrode sheet and assembled into a 2032-type button half-cell for testing.

[0078] The preparation method of the button half-cell is as follows: the germanium-based negative electrode material, the conductive additive carbon black, and the adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) are weighed according to a mass ratio of 92%:3%:5%, and the slurry is prepared with a beater, and then coated, dried, and cut into pieces, and assembled into a button half-cell in a glove box.

[0079] The prepared button half-cell was tested in constant current charge and discharge mode using a charge and discharge instrument. The test conditions were: the charge and discharge cut-off voltages were 2V and 0.005V, respectively. After that, it was activated at a rate of 0.05C, and the charge and discharge cycle test was performed at a rate of 0.5C. The coulomb efficiency of the first cycle of the test was 94.6%.

[0080] Example 2

[0081] This embodiment provides a preparation process and performance test of a germanium-based negative electrode material. The specific preparation process is as follows.

[0082] (1) At room temperature, 2.5 kg of porous polyaniline is placed in a deposition chamber of a vapor deposition furnace, and nitrogen is introduced into the vapor deposition furnace to exhaust air; wherein the porosity of the porous polyaniline is 45%, and the pore size of the porous polyaniline is in the range of 10 nm to 36 nm.

[0083] (2) Turn off the nitrogen for evacuation, raise the temperature to 360° C., and introduce a mixed gas of germane, vaporized silicon germanium and nitrogen in a mass ratio of 2:1:1 into the deposition chamber for 1 hour. The germanium obtained by decomposing germane at 360° C. is deposited in the pores of the porous polyaniline, and the vaporized silicon germanium is directly deposited in the pores of the porous polyaniline to form a silicon-germanium alloy. The mixture is then calcined at 560° C. for 4 hours to obtain a germanium-based composite material.

[0084] (3) The above germanium-based composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer on the surface of the germanium-based composite material. The specific method is as follows: 2.5 kg of the germanium-based composite material is placed in a rotary kiln, the temperature is raised to 360° C. under a nitrogen atmosphere, argon gas and acetylene gas are introduced at a volume ratio of 1:1.5 for gas phase coating, the organic gas source is turned off after keeping the temperature for 3 hours, the material is cooled to room temperature and then discharged and classified to obtain a germanium-based negative electrode material with a core-shell structure.

[0085] The mass percentage of single-substance germanium to the total mass of the germanium-based negative electrode material is 3.8%, and the mass percentage of silicon-germanium alloy to the germanium-based negative electrode material is 2.5%.

[0086] The germanium-based negative electrode material prepared in this embodiment was used to prepare a negative electrode sheet and assembled into a 2032-type button half-cell for testing.

[0087] The preparation method of the button half-cell is as follows: the germanium-based negative electrode material, the conductive additive carbon black, and the adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) are weighed according to a mass ratio of 92%:3%:5%, and the slurry is prepared with a beater, and then coated, dried, and cut into pieces, and assembled into a button half-cell in a glove box.

[0088] The prepared button half-cell was tested in constant current charge and discharge mode using a charge and discharge instrument. The test conditions were: the charge and discharge cut-off voltages were 2V and 0.005V, respectively. After that, the cell was activated at a rate of 0.05C and then the charge and discharge cycle test was performed at a rate of 0.5C. The coulomb efficiency of the first cycle of the test was 94.1%.

[0089] Example 3

[0090] This embodiment provides a preparation process and performance test of a germanium-based negative electrode material. The specific preparation process is as follows.

[0091] (1) At room temperature, 2.5 kg of porous polyaniline is placed in a deposition chamber of a vapor deposition furnace, and nitrogen is introduced into the vapor deposition furnace to exhaust air; wherein the porosity of the porous polyaniline is 25%, and the pore size of the porous polyaniline is in the range of 10 nm to 42 nm.

[0092] (2) Turn off the nitrogen gas used for evacuation, raise the temperature to 360° C., and introduce a mixed gas of germane, vaporized tin germanium and nitrogen in a mass ratio of 2:1:1 into the deposition chamber for 1 hour. The germanium obtained by decomposing germane at 360° C. is deposited in the pores of the porous polyaniline, and the vaporized tin germanium is directly deposited in the pores of the porous polyaniline to form a tin-germanium alloy. The mixture is then calcined at 560° C. for 4 hours to obtain a germanium-based composite material.

[0093] (3) The above germanium-based composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer on the surface of the germanium-based composite material. The specific method is as follows: 2.5 kg of the germanium-based composite material is placed in a rotary kiln, the temperature is raised to 360° C. under a nitrogen atmosphere, argon gas and acetylene gas are introduced at a volume ratio of 1:1.5 for gas phase coating, the organic gas source is turned off after keeping the temperature for 3 hours, the material is cooled to room temperature and then discharged and classified to obtain a germanium-based negative electrode material with a core-shell structure.

[0094] The mass percentage of germanium to the total mass of the germanium-based negative electrode material is 3.7%, and the mass percentage of the tin-germanium alloy to the germanium-based negative electrode material is 4.8%.

[0095] The germanium-based negative electrode material prepared in this embodiment was used to prepare a negative electrode sheet and assembled into a 2032-type button half-cell for testing.

[0096] The preparation method of the button half-cell is as follows: the germanium-based negative electrode material, the conductive additive carbon black, and the adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) are weighed according to a mass ratio of 92%:3%:5%, and the slurry is prepared with a beater, and then coated, dried, and cut into pieces, and assembled into a button half-cell in a glove box.

[0097] The prepared button half-cell was tested in constant current charge and discharge mode using a charge and discharge instrument. The test conditions were: the charge and discharge cut-off voltages were 2V and 0.005V, respectively. After that, it was activated at a rate of 0.05C, and the charge and discharge cycle test was performed at a rate of 0.5C. The coulomb efficiency of the first cycle of the test was 94.2%.

[0098] Comparative Example 1

[0099] This embodiment provides a preparation process and performance test of a negative electrode material. The negative electrode material is different from that of Embodiment 1 in that porous SiC is used as a matrix instead of porous polyaniline. The raw materials and process parameters used in other preparation processes are the same as those of Embodiment 1.

[0100] The negative electrode material prepared in this comparative example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as those in Example 1. The coulomb efficiency of the first cycle of the test was 93.2%.

[0101] Comparative Example 2

[0102] This embodiment provides a process for preparing a negative electrode material. The negative electrode material is different from that in Embodiment 1 in that it does not have a carbon coating layer. The raw materials and process parameters used in other preparation processes are the same as those in Embodiment 1.

[0103] The negative electrode material prepared in this comparative example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as those in Example 1. The coulomb efficiency of the first cycle of the test was 89.7%.

[0104] Comparative Example 3

[0105] This embodiment provides a process for preparing a negative electrode material. The negative electrode material is different from that of Embodiment 1 in that step (2) is not performed. The raw materials and process parameters used in other preparation processes are the same as those of Embodiment 1.

[0106] The negative electrode material prepared in this comparative example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as those in Example 1. The coulomb efficiency of the first cycle of the test was 84.1%.

[0107] By comparing the data, it can be seen that the first-cycle coulombic efficiency of the button-type half-cells of Examples 1-3 is greater than that of Comparative Examples 1-3. This is because the germanium-based negative electrode material prepared in the examples of the present invention is a germanium-based composite material obtained by depositing the germanium / silicon-germanium alloy and / or tin-germanium alloy obtained from the decomposed germane in the pores of porous polyaniline by vapor deposition, and then the germanium-based composite material is subjected to carbon coating treatment to finally obtain a germanium-based negative electrode material, wherein the porous polyaniline matrix has polar groups (-NH- and =N-) that can promote the adsorption and intercalation of lithium ions or sodium ions, thereby increasing the active sites of the negative electrode material, which can significantly improve the energy density and electrochemical activity of the battery; at the same time, the carbon coating layer can make the germanium-based negative electrode material have high cycle stability; the germanium particles obtained by decomposition and deposition of germane have a smaller particle size and anisotropic expansion, while maintaining the structural integrity of the material well. Under the synergistic effect of these three aspects, the germanium-based negative electrode materials prepared in Examples 1-3 of the present invention have a higher first-cycle coulombic efficiency when used in a battery.

[0108] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A germanium-based negative electrode material, characterized in that: The germanium-based negative electrode material comprises: germanium-based composite particles and a carbon coating layer coated on the outer surface of the germanium-based composite particles; The pores of the porous polyaniline form continuous channels and spaces inside the porous polyaniline, so that the germanium-containing sediment is deposited in the pores of the porous polyaniline to form the germanium-based composite particles; in the germanium-based composite particles, the porous polyaniline accounts for 15%-95% by mass; the germanium-containing sediment includes at least a single substance of germanium, and may also include or exclude a silicon-germanium alloy and / or a tin-germanium alloy; In the germanium-based negative electrode material, the mass percentage of the germanium-based composite particles is 85%-99%; The mass percentage of the germanium single substance in the germanium-based negative electrode material is 0.1%-80%; the mass percentage of the silicon-germanium alloy in the germanium-based negative electrode material is 0-15%; the mass percentage of the tin-germanium alloy in the germanium-based negative electrode material is 0-15%; The polar groups -NH- and =N- of the porous polyaniline are used to promote the adsorption and intercalation of lithium ions or sodium ions, thereby increasing the active sites of the negative electrode material and improving the electrochemical activity during the charge and discharge process of the battery.

2. The germanium-based negative electrode material according to claim 1, characterized in that: The particle size D of the porous polyaniline 50 The diameter of the pores of the porous polyaniline is between 50nm and 50μm; the pore size of the pores of the porous polyaniline is between 1nm and 300nm; and the porosity of the porous polyaniline is between 20% and 90%.

3. The germanium-based negative electrode material according to claim 1, characterized in that: The mass of the germanium single substance accounts for 3%-30% of the total mass of the germanium-based negative electrode material; The mass of the carbon coating layer accounts for 1%-15% of the total mass of the germanium-based negative electrode material; The germanium-based composite material is obtained by decomposing a germanium source material by vapor deposition and depositing a germanium-containing precipitate in the pores of the porous polyaniline; the germanium source material at least includes germane and may include or exclude vaporized silicon germanium and / or vaporized tin germanium.

4. A method for preparing the germanium-based negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The porous polyaniline is placed in a deposition chamber of a vapor deposition furnace and an inert environment is maintained; A mixed gas of a germanium source material and an inert gas is introduced into a deposition chamber, and the germanium source material forms a germanium-containing precipitate which is deposited in the pores of the porous polyaniline to obtain germanium-based composite particles; The germanium-based composite material particles are subjected to carbon coating treatment in a coating furnace to form a carbon coating layer, thereby obtaining a germanium-based negative electrode material.

5. The preparation method according to claim 4, characterized in that: The germanium source material at least includes germane, and may also include or exclude vaporized silicon germanium and / or vaporized tin germanium; The inert gas includes nitrogen and / or argon; the time for introducing the mixed gas is 30 minutes to 12 hours; The mass ratio of the germanium source material to the inert gas in the mixed gas is 1:1-1:

10.

6. The preparation method according to claim 5, characterized in that: When the germanium source material only includes germane, the step of introducing a mixed gas of the germanium source material and an inert gas into the deposition chamber, wherein the germanium source material forms a germanium-containing precipitate which is deposited in the pores of the porous polyaniline, and obtaining the germanium-based composite particles is specifically as follows: introducing a mixed gas of germane and an inert gas into the deposition chamber, maintaining the temperature at 350° C.-360° C., decomposing germane into a single germanium substance, wherein the single germanium substance is deposited in the pores of the porous polyaniline, and then calcining at 560° C. to obtain the germanium-based composite material; When the germanium source material only includes germane and vaporized silicon germanium and / or vaporized tin germanium, a mixed gas of the germanium source material and an inert gas is introduced into a deposition chamber, and the germanium source material forms a germanium-containing sediment which is deposited in the pores of the porous polyaniline to obtain germanium-based composite particles. Specifically, the following steps are performed: a mixed gas of germane and vaporized silicon germanium and / or vaporized tin germanium and an inert gas is introduced into the deposition chamber, and the chamber is kept warm at 350°C-360°C to decompose germane into a single germanium substance, and the single germanium substance is deposited in the pores of the porous polyaniline together with the silicon germanium / tin germanium, and then calcined at 560°C to obtain a germanium-based composite material.

7. The preparation method according to claim 4, characterized in that: The carbon coating treatment method includes: one of gas phase coating, liquid phase coating or solid phase coating; The mass of the carbon coating layer accounts for 1%-15% of the total mass of the germanium-based negative electrode material; The carbon material used for the liquid phase coating or solid phase coating includes one or more of glucose, sucrose, liquid asphalt, phenolic resin, polyvinylidene fluoride, citric acid, polyacrylonitrile, and polyvinyl alcohol; The carbon material used for gas phase coating includes one or more of methane, ethylene, propylene, acetylene and natural gas.

8. A negative electrode plate, characterized in that: The negative electrode plate comprises the germanium-based negative electrode material described in any one of claims 1 to 3.

9. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet as claimed in claim 8.

10. The secondary battery according to claim 9, characterized in that: The secondary batteries include lithium ion batteries and sodium ion batteries.

Citation Information

Patent Citations

  • Sodion battery cathode material

    CN102709534A

  • Negative electrode material of lithium ion battery, preparation method thereof and lithium ion battery

    CN112635733A

  • Alloyed negative electrode material and preparation method and application thereof

    CN116581282A